Sartoris: an experiment regarding microkernel-based operating systems - Bazerque, S. (2002)
Sartoris is a minimal, portable microkernel. It provides direct support for the creation and destruction of tasks and threads, and inter-task communication mechanisms (message queues and shared memory). However, it attempts to be as policy-neutral as possible, providing a high degree of freedom to the operating system designer. In this article we discuss design issues and implementation strategies for the x86 family of processors. Finally, we describe a small Sartoris-based operating system, that was created to test the microkernel.